DEMOCRACY, ISLAM, AND RELIGIOUS FREEDOM IN INDONESIA: A SHORT POLITICAL AND RELIGION HISTORY - Saiful Hakam (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2016)
Indonesia, even though state gives a concession on moderate on religious matter, the phenomena shows that the radical Islamic group tries to intervene religious matter in Indonesia. Thus it might dangerous to manage the diversity that becomes national emblem. In this paper, I argue that democratic society should regulate and control religious activity. I have two reasons about it. My reasons are based on Indonesian experiences. First, the democratic society prevents activities of a majority religion that contain radical political activities and tried to force their values to other citizens.. The Second is the democratic society has a strong idea to protect minority and their religions.